Handbook of the Social Psychology of Inequality
XXV, 749 p.
Keywords: This handbook provides the first comprehensive overview of social psychological research on inequality for a graduate student and professional audience. Drawing on all of the major theoretical traditions in sociological social psychology, its chapters demonstrate the relevance of social psychological processes to this central sociological concern. Each chapter in the handbook has a distinct substantive focus, but the chapters will also share common emphases on: - The unique contributions of sociological social psychology - The historical roots of social psychological concepts and theories in classic sociological writings - The complementary and conflicting insights that derive from different social psychological traditions in sociology. This Handbook is of interest to graduate students preparing for careers in social psychology or in inequality, professional sociologists, and university/college libraries .